Mobility Models and Efficient Multihop Routing Methods in MANETs - Abed, Abdul Karim (My University, 2013)
Many routing protocols are proposed in the literature on mobile ad hoc networks (MANETs). Some of those protocols which have been investigated under different assumptions are unable to capture the actual characteristics of MANETs. Therefore, there is a necessity to investigate the performance of MANETs under a number of different protocols with various mobility models. The first part of this study evaluates the performance of the single path routing protocols Ad hoc On Demand Distance Vector (AODV), Dynamic Source Routing Protocol (DSR) and Destination Sequenced Distance Vector (DSDV), in the presence of different network loads and under four well-known mobility models, which are the Random Waypoint Mobility Model (RWPM), the Gauss Markov Mobility Model (GMM), the Manhattan Grid Mobility Model (MGM), and the Random Point Group Mobility Model (RPGM). Our findings show that DSR routing protocol has a better performance compared to other protocols with respect to various metrics. In the second part of my thesis, a new mobility model has been implemented and investigated with a multipath routing protocol. Our proposed model partitions an area under simulation into clusters. An extensive simulation has been conducted to investigate the performance of the proposed model, together with well known mobility models with Ad hoc On-demand Multipath Distance Vector (AOMDV) routing protocol to be utilized in different network clusters (ad hoc configurations). Using the simulation results, we are able to formulate a novel mobility model that could be used with different routing protocols. Keywords: Wireless mobile ad hoc networks, routing protocols, mobility modeling, performance.

ÖZ: Literatürde, hareketli özel amaca yönelik ağlar (MANETs) üzerinde birçok yönlendirme protokolleri önerilmiştir. Farklı varsayımlar altında incelenen bazı protokollerle MANET’lerin gerçek özelliklerini yakalamak mümkün değildir. Bu nedenle, MANET’lerin performansını farklı protokoller ile farklı hareketlilik modelleri kullanılarak araştırma zorunluluğu vardır. Bu çalışmanın ilk bölümünde, tek yollu yönlendirme protokollerinden özel amaca yönelik talebe bağlı mesafe vektörü (AODV) protokolü, dinamik kaynak yönlendirme (DSR) protokolü ve hedef sıralı uzaklık vectorü (DSDV) protokolünün performansı farklı ağ yapılarında, iyi bilinen dört hareketlilik modellerinden olan, rastgele geçiş noktası hareketlilik modeli (RWPM), Gauss Markov hareketlilik modeli (GMM), Manhattan ızgara hareketlilik odeli (MGM) ve rastgele nokta grup hareketlilik modeli (RPGM) ile birlikte değerlendirilmiştir. Bulgularımız, DSR yönlendirme protokolünün performansının farklı ölçütlerde diğer protokollere göre daha iyi olduğunu göstermektedir. Tezin ikinci bölümünde ise, yeni bir hareketlilik modeli çok yollu bir yönlendirme protokolü ile uygulanmış ve incelenmiştir. Önerilen model benzetim alanını parçalayarak kümelere (clusters) böler. Önerilen modelin performansını araştırmak için, özel amaca yönelik talebe bağlı çokyollu mesafe vektörü (AOMDV) protokolü iyi bilinen hareketlilik modelleri ile farklı özel amaca yönelik ağ yapılarında kapsamlı simulasyonlar yapılmıştır. Elde edilen benzetim sonuçlarından, farklı yönlendirme protokolleri ile kullanılabilecek yeni bir hareketlilik modeli formüle edebiliceğimiz ortaya çıkmıştır. Anahtar Kelimeler: Kablosuz hareketli özel amaca yönelik ağlar, yönlendirme protokolleri, hareketlilik modelleme, performans.
Doctor of Philosophy in Computer Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2013. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Wireless communication systems; Wireless networks; Wireless mobile ad hoc networks; routing protocols; mobility modeling; performance